Procedures for Imposing Disciplinary Punishment According to the Iraqi Amended Law of Discipline of State Employees and the Public Sector No. 14 Of 1991 - Jenan A. Fattah (Journal of Madenat Alelem University College, 2016)
The importance of searching in the procedures for imposing tunable penalty is clear in that the administration is committed to give the employee an essential guarantee in following justice procedures in the inquiry. this justice realized from that the administration is obliged to follow and observe some procedures precedes the decision of imposing the tunable penalty or it becomes illegal. The tunable investigation as a procedure must be followed by the administration is considered a guarantee for the employee and a tool to get the reality of Incidents alleged against him. Also, the investigation will not be only after the of the employee accused of an offense to an investigation committee to investigate with him and must follow all the formality procedures legally obliged.to ensure that the law of the discipline of civil servants and public sector provision eliminates the need to compel the minister or head of the department as a formality formation of an investigative committee to look violation attributed to the employee without leaving them a choice between the formation of the investigative or interrogation in penalties (to draw attention, warning, cut salary), but the composition of the investigative committee was bond on the administrative head of all disciplinary sanctions to ensure the fairness of the disciplinary accountability.